An improved picosecond-level laser time transfer for China’s space station - Renfang Geng; Zhibo Wu; Yong Huang; Kai Tang; Haifeng Zhang; Wendong Meng; Zhien Cheng; Yanming Guo; Shuaihe Gao; Wenbin Wang; Xinyuan Mao; Tong Liu; et al. (Journal of Geodesy, 2026)
The development of techniques for the comparison of remote clocks plays an important role in metrology and fundamental science. Recent progress in the domain of ground-based and space-based atomic clocks requires important improvements in existing time and frequency transfer links. Here, we propose a satellite-based improved laser time transfer (ILTT) scheme based on existing satellite laser ranging (SLR) technique, which has been deployed on the Mengtian Laboratory Module of China’s Space Station (CSS). The ILTT payload comprises a single-photon avalanche diode (SPAD), a multi-level optimized optical system, an event timer, and a laser retroreflector array (LRA). A repetition rate of 10 kHz is adopted to improve normal-point precision. Laboratory experiments demonstrate that the time deviation (TDEV) of the entire ILTT system was better than 1 ps at 1 s and 0.6 ps at 100,000 s. In addition, we introduce a relativistic laser time transfer model and evaluate the impact of relativistic frequency shift terms on time transfer stability, meeting the requirements of the high-precision time–frequency rack (HTFR) mission aboard the CSS. In the on-orbit experiments, we have achieved state-of-the-art satellite-to-ground time synchronization with a precision of 2–5 ps at 1 s and a TDEV of 0.7 ps at 50 s. This approach is also sufficient for future time transfer links to geosynchronous and cislunar orbits.